Assessment of multiple types of DNA damage in human placentas from smoking and nonsmoking women in the Czech Republic - Pratt, M Margaret; King, Leon C; Adams, Linda D; John, Kaarthik; Sirajuddin, Paul; Olivero, Ofelia A; Manchester, David K; Sram, Radim J; DeMarini, David M; Poirier, Miriam C (Environmental and molecular mutagenesis, 2011)
Three classes of DNA damage were assessed in human placentas collected (2000-2004) from 51 women living in the Teplice region of the Czech Republic, a mining area considered to have some of the worst environmental pollution in Europe in the 1980s. Polycyclic aromatic hydrocarbon (PAH)-DNA adducts were localized and semiquantified using immunohistochemistry (IHC) and the Automated Cellular Imaging System (ACIS). More generalized DNA damage was measured both by (32)P-postlabeling and by abasic (AB) site analysis. Placenta stained with antiserum elicited against DNA modified with 7β,8α-dihydroxy-9α,10α-epoxy-7,8,9,10-tetrahydro-benzo[a]pyrene (BPDE) revealed PAH-DNA adduct localization in nuclei of the cytotrophoblast (CT) cells and syncytiotrophoblast (ST) knots lining the chorionic villi. The highest levels of DNA damage, 49-312 PAH-DNA adducts/10(8) nucleotides, were found by IHC/ACIS in 14 immediately fixed placenta samples. An additional 37 placenta samples were stored frozen before fixation and embedding, and because PAH-DNA adducts were largely undetectable in these samples, freezing was implicated in the loss of IHC signal. The same placentas (n = 37) contained 1.7-8.6 stable/bulky DNA adducts/10(8) nucleotides and 0.6-47.2 AB sites/10(5) nucleotides. For all methods, there was no correlation among types of DNA damage and no difference in extent of DNA damage between smokers and nonsmokers. Therefore, the data show that DNA from placentas obtained in Teplice contained multiple types of DNA damage, which likely arose from various environmental exposures. In addition, PAH-DNA adducts were present at high concentrations in the CT cells and ST knots of the chorionic villi.
Keywords: DNA Adducts; Smoking; kouření; adukty DNA; techniky in vitro; Immune Sera; Keratinocytes; lidé; Polycyclic Aromatic Hydrocarbons; Czech Republic; In Vitro Techniques; poškození DNA; těhotenství; Česká republika; imunohistochemie; Pregnancy; DNA Damage; ženské pohlaví; keratinocyty; antisérum; Immunohistochemistry; Humans; polycyklické aromatické uhlovodíky; Female